2007
DOI: 10.1093/ndt/gfm011
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus after kidney transplantation: a French multicentre observational study

Abstract: NODM is associated with certain RFs present prior to kidney transplantation, and with treatment with Tac as opposed to CsA-ME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 23 publications
4
52
2
1
Order By: Relevance
“…In this study, a significant interaction (P = 0.0001) was found between presence of HCV and use of tacrolimus, since in the HCV-positive group, T2D occurred more often in tacrolimus-treated than cyclosporine A-treated patients (57.8% vs 7.7%; P < 0.0001) [55] . Most subsequent studies confir med this robust association [56][57][58][59][60][61][62][63] , with some exceptions [21,[64][65][66] . Thus, in a recent meta-analysis of 10 studies, the pooled relative risk for post-KT T2D was 2.73 (95% CI: 1.94-3.83) [67] .…”
Section: Association Between Hcv and T2dmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, a significant interaction (P = 0.0001) was found between presence of HCV and use of tacrolimus, since in the HCV-positive group, T2D occurred more often in tacrolimus-treated than cyclosporine A-treated patients (57.8% vs 7.7%; P < 0.0001) [55] . Most subsequent studies confir med this robust association [56][57][58][59][60][61][62][63] , with some exceptions [21,[64][65][66] . Thus, in a recent meta-analysis of 10 studies, the pooled relative risk for post-KT T2D was 2.73 (95% CI: 1.94-3.83) [67] .…”
Section: Association Between Hcv and T2dmentioning
confidence: 95%
“…The existing publication bias did not change the results in a meaningful way, after a sensitivity analysis was performed [67] . In addition to ongoing HCV infection, risk factors for developing T 2 D a f t e r K T a r e f a m i l y h i s t o r y o f T 2 D [ 5 5 , 6 0 ] , age [57,59,61,62] , use of tacrolimus [55,59,60,62,63] , smoking [61] , overweight/obesity [62,63] , African-American ethnicity [62] and pre-transplantation impaired fasting glucose [63] . Thus, there exists a significant increase of the risk of post-KT T2D in HCV-positive recipients, especially in the first 2 mo after transplantation [57] .…”
Section: Association Between Hcv and T2dmentioning
confidence: 99%
“…[24] Other studies have also identified tacrolimus as a risk factor for posttransplantation diabetes in addition to older age (> 40 years), Body Mass Index greater than 25 kg/m 2 , positive hepatitis C serology, family history of diabetes, metabolic syndrome, African-American or Hispanic race-ethnicity, and higher mean pretransplantation plasma glucose concentration. The risk factors for posttransplantation diabetes are similar to those for type 2 diabetes (Markell, 2004;González-Posada at al., 2004;Kamar et al, 2007). Hypertension (38-89%) is common, as is drug-induced diabetes (24%), exacerbated by the use of corticosteroids.…”
Section: Adverse Reactionsmentioning
confidence: 99%
“…Patients who receive tacrolimus have been reported to be about 5 times more likely to develop NODM than those who receive cyclosporin (CyA). 9 Kamar et al 8 reported prevalences of NODM of 10.2% v. 3.8% (tacrolimus v. CyA), and Cho et al 10 found a prevalence of 57.1% with tacrolimus at 6 months after transplantation. A South African review 11 of 17 patients receiving tacrolimus found that 47% became diabetic.…”
Section: New-onset Diabetes Mellitus After Renal Transplantation New-mentioning
confidence: 99%